Emerging best practices for supporting temporary migrant farmworkers in Western Canada. (11th July 2020) - Caxaj, C. Susana; Cohen, Amy
Abstract: The aim of this study was to examine the role of support people in determining migrant agricultural workers' access to, or ability to navigate, public spaces and services. While the role of support networks for this population is still in its infancy, much can be gained from understanding the emerging best practices for helping this group. Using a situational analysis research approach, we carried out 4 focus groups and 25 one‐on‐one interviews, recruiting a total of 30 informal and formal support people as study participants between 2018 and 2019. Data analysis occurred over a 2‐year period largely simultaneously with data collection. Developing analytic maps as outlined by Clarke's approach to situational analysis, we reviewed texts and preliminary codes by organising them in terms of situations, social worlds, and discursive positions. Ultimately, we identified four best practices: (a) Anticipating and addressing barriers; (b) building trust and community; (c) acknowledging rights and system accountability and (d) bearing witness and looking to the future. Underlying these best practices was the need for support people to display 'support readiness', or specialised skills, motivation and a personal connection to migrant farmworkers. While these practices have the potential to improve migrant workers' ability to fully participate in public spaces and access public services, until systemic constraints are addressed, support people will be unable to fill the gaps in support for this population.